Penerapan Lean Manufacturing untuk Mereduksi Waste pada Proses Produksi Celana Jeans di PT. X - Maulana Muwahid, Irfan; R. Muhammad, Chaznin; Amaranti, Reni (UNISBA Press, 2023)
Abstract. PT. X is a garment company in the city of Bandung that produces various types of clothing. This research focuses on one of the company's products, namely jeans. The results of observations on the jeans production process found some waste (waste) consisting of excessive transportation, repeated inspection processes, lots of unused materials and goods, and waiting employees. This waste has an impact on production lead times that are getting longer. Therefore, this study aims to reduce waste (waste) that occurs in the production process of jeans. Improvements made are by utilizing the concept of Lean Manufacturing, assisted by Value Stream Mapping (VSM) tools, Seven Waste Questionnaire, Value Stream Mapping Analysis Tools (VALSAT), and cause and effect diagrams (Fishbone). The results of weighting waste using the Seven Waste questionnaire, obtained the three most influential types of waste, namely Excess Processing at 31.40%, Transportation at 22.09%, and Unnecessary Inventory at 16.28%, followed by other types of waste namely Waiting by 11.63%, Unnecessary Motion by 9.30%, Defect by 8.14%, and Overproduction by 1.16%. Proposals for improvements were made only for the three most influential reductions in types of waste (waste), namely by designing visual work standards, redesigning layouts, and implementing a 5S work culture. The result of implementing the improvement was a reduction in the total Production Lead Time in the Future State by 108.95 minutes, thereby increasing Process Cycle Efficiency (PCE) by 18.92%, from 57.26% to 76.19%. Keywords: Waste, Lean Manufacturing, Value Stream Mapping (VSM) Abstrak. PT. X merupakan perusahaan garmen di Kota Bandung yang memproduksi berbagai jenis pakaian. Penelitian ini berfokus pada salah satu produk perusahaan yaitu celana jeans. Hasil observasi pada proses produksi celana jeans ditemukan beberapa pemborosan (waste) yang terdiri dari transportasi berlebihan, proses pemeriksaan secara berulang, penumpukan bahan dan barang tidak terpakai, serta karyawan yang menunggu. Pemborosan (waste) tersebut berdampak pada lead time produksi yang semakin panjang. Oleh karena, penelitian ini bertujuan untuk mereduksi pemborosan (waste) yang terjadi pada proses produksi celana jeans. Upaya perbaikan yang dilakukan adalah dengan memanfaatkan konsep Lean Manufacturing, dibantu dengan tools Value Stream Mapping (VSM), Kuesioner Seven Waste, Value Stream Mapping Analysis Tools (VALSAT), serta diagram sebab akibat (Fishbone). Hasil pembobotan pemborosan (waste) menggunakan kuesioner Seven Waste, didapatkan tiga jenis pemborosan (waste) paling berpengaruh yaitu Excess Processing sebesar 31,40%, Transportation sebesar 22,09%, serta Unnecessary Inventory sebesar 16,28%, diikuti oleh jenis pemborosan lain yaitu Waiting sebesar 11,63%, Unecessary Motion sebesar 9,30%, Defect sebesar 8,14%, serta Overproduction sebesar 1,16%. Usulan perbaikan yang dibuat untuk mereduksi tiga jenis pemborosan (waste) paling berpengaruh yaitu dengan perancangan standarisasi kerja visual, perancangan ulang layout, serta penerapan budaya kerja 5S. Hasil penerapan usulan perbaikan adalah berkurangnya total Production Lead Time pada Future State sebesar 108,95 menit, sehingga meningkatkan Process Cycle Efficiency (PCE) sebesar 18,92% yaitu dari 57,26% menjadi 76,19%. Kata Kunci: Waste, Lean Manufacturing, Value Stream Mapping (VSM)